Implementation of Family Program Policies Hope in Handling Poverty in the City - Sylvab, Waribugo (Decision, 2024)
The Family Hope Program (PKH) is a conditional social assistance program launched in 2007 to help poor and vulnerable families overcome poverty in Indonesia. Recipients must be registered in the Integrated Social Welfare Data (DTKS). The purpose of this study is to show how the Family Hope Program Policy was implemented in Bandung City by using communication, resources, disposition, and bureaucratic structure to address poverty issues. This study employs the literature review approach and previous research that is undoubtedly relevant to the debate of the implementation of the Family Hope Program Policy in Bandung City. The data were then evaluated using Edward III's (1980) implementation model, which revealed four elements that influence policy execution: communication, resources, disposition, and bureaucratic structure. The results showed that the Bandung City Family Hope Program policy is being implemented effectively. However, there are still hurdles, such as delivery of impediments from the regional coordinator to the center or the social ministry. Because there is no proof of reporting, it solely communicates via digital messaging. Furthermore, the obstacles arise from the usage of suboptimal social benefit cards. The lack of PKH professionals is perceived to be unequal in task distribution. Furthermore, there are insufficient infrastructure facilities to support the operation of the PHK companion.